INCREASING STUDENTS LISTENING SKILLS THROUGH SONG AND AUTHENTIC VIDEO - Srirejeki, Ni Luh Komang Galih; Darmayanti, Putu Sri (Institut Hindu Dharma Negeri Denpasar, 2019)
The research aimed to investigate whether the usage of songs and authentic videos were able to increase students listening ability. The purpose was to find out whether the students who taught by songs and authentic videos achieved better improvement to compare to those who did not. Most of the researchers used experimental methods. The questionnaire and data collection were used to analyze how this activity affected. The students who were taught using song and authentic video got better outcomes rather than those who were taught using the usual. The questionnaire responses showed that the students preferred the authentic listening materials. Those were more interesting and more related to their real-life context so that it could motivate them to give more attention to the listening class and this also assisted them to improve their listening ability.